2021
DOI: 10.1039/d1fo00956g
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal digestion of dietary advanced glycation endproducts increases their pro-inflammatory potential

Abstract: Digestion of dietary advanced glycation endproducts (dAGEs) increases its pro-inflammatory potential in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Previously, a series of studies had reported clues that simulated digestion of high-AGE foods such as cookies and glycated proteins such as GO-glycated BSA generated extra amounts of AGEs in GI digests. 21–23,42 This study, for the first time, through establishing a co-digestion model with whey proteins and α-DCs, evidenced the hypothesis that typical AGEs are additionally formed between MR intermediates and substrates released from proteolysis along the GI tract. Further exploration using simplified glycation systems such as synthesized peptides are warranted to explain the stoichiometric relationship of the reactions involved.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Previously, a series of studies had reported clues that simulated digestion of high-AGE foods such as cookies and glycated proteins such as GO-glycated BSA generated extra amounts of AGEs in GI digests. 21–23,42 This study, for the first time, through establishing a co-digestion model with whey proteins and α-DCs, evidenced the hypothesis that typical AGEs are additionally formed between MR intermediates and substrates released from proteolysis along the GI tract. Further exploration using simplified glycation systems such as synthesized peptides are warranted to explain the stoichiometric relationship of the reactions involved.…”
Section: Resultsmentioning
confidence: 63%
“…[18][19][20] Interestingly, it was found that in vitro digestion of high-AGE foods like ginger biscuits generated bound-form AGEs in the small intestinal phase. 21,22 Coincidentally, simulated GI digestion of cookies elevated the amounts of MGO and GO by up to almost 700%, particularly in the ones with added fructose. 23 These results clearly point to the possibility that additional glycation reactions take place between α-DCs and susceptible food ingredients along the digestion process.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of these products is thus inevitable, while the potential effect of these products on the body must be clarified. For example, it was proven that dietary AGEs before and after digestion have an ability to promote cellular inflammation in human macrophages [ 26 ]. Along with the previously described investigations, the current study confirmed that the performed lactose glycation of casein reduced the ability of the resultant casein hydrolysate to alleviate LPS-induced cellular inflammation ( Figure 4 and Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been observed that the pro-inflammatory cytokine TNF-α is secreted in RAW 264.7 macrophages in response to the dietary AGEs [ 23 ]. Moreover, AGEs in skimmed milk powder was shown to cause intestinal inflammation in young rats [ 26 ], and the secretion of the inflammatory cytokine TNF-α in human macrophages was enhanced by dietary AGEs [ 59 ]. Sharing a conclusion consistent with the aforementioned studies, this study found that CH in LPS-stimulated cells had an anti-inflammatory effect; however, due to casein glycation of the Maillard-type, GCH showed a lower anti-inflammatory effect than CH and also promoted IL-6 secretion and up-regulation of TLR4/p-p65 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation